Using Finite Element Method in Optimisation of Die Casting Design - Abdewi, Elfetori F. (1999)
Die casting process is one of the widely used processes in the manufacturing area. It has the capability for high production rates with good strength, high quality parts with complex shapes. Die is the main factor which affects the cost of this process. Even when the process is semi or fully automated the cost of the die is proportionately high. To design an optimum die, it has been understood that it is very difficult to achieve the target practically without prior prediction. It needs continuous monitoring of the process, starting from the first shot until the failure of the die. Even then it cannot be said that, the die has been optimised to produce a particular part. To decide so, several tests should be carried out on the same part. As this will be very costly, it would be unwise to do it. But in the presence o f theoretical analysis, the number of tests will be reduced. For these reasons the Finite Element Analysis (FEA) would appear to be well suited to investigate the response of such system to structure and potential loading. Such a computational investigation is the subject of this re search. Commercially available FE A So ftware (LUSAS) ha s been used. A full Finite Element Analysis was carried out in order to achieve an optimum design, and to predict the die life. The analysis has been repeated several time s for different elements to achieve the best possible design. Since ca sting is a repetitive manufacturing process, fatigue load was taken into consideration and analysis carried out for a high number of cycles.